Socio-Cultural Integration in Mergers and Acquisitions The Nordic Approach (Springer International Publishing, 2018)
'I am happy and proud to see Nordic scholars playing a central role in advancing state-of-the-art knowledge in this important area of management and organization research. A must-read for all interested in Nordic mergers and acquisitions.' Eero Vaara, Professor, Aalto University, Finland Taking a fresh and much-needed perspective on the management of international acquisitions, this book focuses on socio-cultural integration, and in particular the importance of emotions and values. The authors build on the human-centric and typically Nordic approach to mergers and acquisitions by presenting rich empirical cases of cross-border acquisitions conducted by leading Nordic multinationals. This book goes beyond merely stating that successful human integration leads to sociocultural convergence and presents how this can actually be accomplished. The authors offer theoretical approaches and practical solutions which have the potential of improving employee motivation and well-being, and in doing so, ultimately enhancing the chances of successful acquisition outcomes. Providing concrete examples of successful practices for managing socio-cultural integration and facilitating employee commitment, this book will appeal to both scholarly and practitioner audiences. Johanna Raitis is a Postdoctoral Researcher at the University of Turku, Finland. Riikka Harikkala-Laihinen is a doctoral candidate in the School of Economics at the University of Turku, Finland. Mélanie E. Hassett is a lecturer in International Business in the Management School of Sheffield University, UK. Niina Nummela is Professor in International Business in the School of Economics at the University of Turku, Finland.